Measuring Local Public Health and Primary Care Collaboration: A Practice-Based Research Approach. Issue 4 (July 2019) - Gyllstrom, Elizabeth; Gearin, Kimberly; Nease, Donald; Bekemeier, Betty; Pratt, Rebekah
Abstract : Objective: To describe the degree of public health and primary care collaboration at the local level and develop a model framework of collaboration, the Community Collaboration Health Model (CCHM). Design: Mixed-methods, cross-sectional surveys, and semistructured, key informant interviews. Setting: All local health jurisdictions in Colorado, Minnesota, Washington, and Wisconsin. Participants: Leaders from each jurisdiction were identified to describe local collaboration. Eighty percent of local health directors completed our survey (n = 193), representing 80% of jurisdictions. The parallel primary care survey had a 31% response rate (n = 128), representing 50% of jurisdictions. Twenty pairs of local health directors and primary care leaders participated in key informant interviews. Main Outcome Measure(s): Thirty-seven percent of jurisdictions were classified as having strong foundational and energizing characteristics in the model. Ten percent displayed high energizing/low foundational characteristics, 11% had high foundational/low energizing characteristics, and 42% of jurisdictions were low on both. Results: Respondents reported wide variation in relationship factors. They generally agreed that foundational characteristics were present in current working relationships but were less likely to agree that relationships had factors promoting sustainability or innovation. Conclusions: Both sectors valued working together in principle, yet few did. Identifying shared priorities and achieving tangible benefits may be critical to realizing sustained relationships resulting in population health improvement. Our study reveals broad variation in experiences among local jurisdictions in our sample. Tools, such as the CCHM, and technical assistance may be helpful to support advancing collaboration. Dedicated funding, reimbursement redesign, improved data systems, and data sharing capability are key components of promoting collaboration. Yet, even in the absence of new reimbursement models or funding mechanisms, there are steps leaders can take to build and sustain their relationships. The self-assessment tool and the CCHM can identify opportunities for improving collaboration and link practitioners to strategies. Abstract : Supplemental Digital Content is Available in the Text.